PENGANGKATAN ANAK SERTA AKIBAT HUKUM TERHADAP PEMBAGIAN WARIS DALAM PERSPEKTIF KOMPILASI HUKUM ISLAM MENURUT INPRES NOMOR 1 TAHUN 1991 TENTANG PENYEBARLUASAN KOMPILASI HUKUM ISLAM - Amelia, Risky; Wahyuni, Nurul (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Adoption is a solution for several couples who have been married for a long time but have not been blessed with a child by God. Behind it all there is a problem, namely that many people do not know the procedures for adopting children, the distribution of inheritance to adopted children, or the position of adopted children's rights in the framework of Islamic inheritance law. There are many problems that occur in society because many people do not know the rights that adopted children have or how to file a legal claim so that the state recognizes them. So this makes it difficult for adopted children to know their position in the eyes of the law.